Modification of Spent Bleaching Earth with WO3 and the Application for Photocatalytic Degradation of Waste Dyestuff under Solar Light (Jurnal Bahan Alam Terbarukan, 2019)
Degradation of blue dye waste in Sarong Samarinda production using WO3-bleaching earth (BE) has been conducted. Structural and morphological characterization has conducted using X-ray diffraction (XRD), and Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDX). The X-ray diffraction results show the mineral on bleaching earth is rectorite dioctahedral mica layer and dioctahedral smectite with a ratio 2:1. The WO3 pattern is appeared after the calcination. After calcination at 500Â°C, the WO3 is deposited homogeneously on the BE surface. The catalytic performance of WO3-BE for photodegradation of the blue dye waste under the solar light is 99.85 % within 1 h.